A chat with Dr. Birama Sidibe, Founder of Agrobiotech, Mali (Episode 1) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
n this video, Dr Sidibe talks about what Agribiotech is about. What they do, what kind of crops they produce and how many years they have been in the crop production space.